SYNTHESIS, CHARACTERIZATION AND PHARMACOLOGICAL SCREENING OF SCHIFF-BASES THROUGH STRUCTURE ACTIVITY RELATIONSHIP (SAR) STUDY IN MICE (Journal of Medical & Health Sciences Review, 2025)
Background: Three benzaldehyde derived Schiff-bases (SH 1-3) were synthesized by the condensation reaction from o-phenylenediamine with their respective benzaldehyde derivatives in absolute ethanolic solution under reflux reaction mixture for 6-8 hrs. The structural determinations of the synthesized Schiff-bases were confirmed by FT-IR and 1H-NMR spectroscopy. Benzaldehyde derived Schiff-bases are well-known to possess potent antioxidant, anxiolytic and sedative potential activities etc. In view of the importance of various benzaldehyde derivatives, the present investigation was undertaken which deals with the structure activity relationship (SAR) study and evaluation of the antioxidant, anxiolytic and sedative potential activities of synthesized Schiff-bases in mice models.Materials and Methods: ABTS scavenging activity was used to assess the antioxidant activity. Acute toxicity test was attained to determine the toxic dose and optimum therapeutic dose. Elevated plus maze model, Light dark model and Hole board test were performed to investigate the anxiolytic effects, while Thiopental induced sleeping time test was executed for the sedative potential ability of synthesized compounds.Results: In SAR study, the results revealed that the synthesized compounds SH 3, SH 2 and SH 1 at dose of 50 mg/kg show potent pharmacological activities like antioxidant, anxiolytic and sedative potential activities respectively as compared to the control group at (p